Why Is the Influence of Sunspot Peaks on the Ocean and Atmosphere in Northern Winter Seen Mainly in the Pacific Region?. (27th December 2011) - van Loon, Harry
Abstract : The sun at sunspot peaks enhances the climatological means in the Pacific region from the stratosphere to the surface of the sea. The robust signal is physically consistent and statistically significant in the 14 sunspot peaks for which sea-level pressure and sea-surface temperature data are available. No other place shows such a strong influence of the sunspot peaks in the northern winter. Why in the Pacific and why a cooling of equatorial surface waters at sunspot peaks? I suggest that in the Indonesian region the strong convection, higher and colder tropopause, warmer water, and Indonesian topography are conducive to channel the solar influence mainly to this region, leading to an enhancement of the Walker and Hadley circulations, expansion and intensification of the dry zone, and cooler equatorial surface waters.